Fear of COVID-19 and secondary trauma: Moderating role of self-efficacy - Li, Yaling; Abbas, Qamar; Manthar, Shahjehan; Hameed, Aftab; Asad, Zainab (Frontiers in Psychology, 2022)
COVID-19 has affected millions of people around the globe. Mental health of people especially the nurses are largely affected by the fear of this virus. The more focus is paid to the vaccination and treatment of this virus, but less attestation is given to heal the mental health of people affected by this virus. The empirical studies supported that different external factors have positive influence on stress recovery, but the external factors are not easily manageable and controllable by the individual. This study preliminary explores the connection between fear of COVID-19 and secondary trauma stress in nurses, and further examines the moderating effects of occupational self-efficacy between the relationship of fear of COVID-19 and secondary traumatic stress. Data for the study was collected from the nurses of 6 large hospitals of Karachi, Pakistan, the final analysis was performed on 243 samples. The results of the study found that nurses in hospitals of Karachi are experiencing secondary traumatic stress due to fear of COVID-19. It was also established that occupational self-efficacy found in these workers, has decreased the strength of fear and has lessen the impact of fear on secondary trauma. Results of this study has both theoretical and practical implications, the managers and hospital administrators may develop stress management programs, offer proper trainings and counselling sessions to the nurses to motivate them emotionally. Developing and promoting occupational self-efficacy amongst nurses may positively result for the patients and community outside the healthcare settings.